2019
DOI: 10.4046/trd.2017.0128
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Characteristics and Prognostic Factors of Lung Cancer in Korea: A Pilot Study of Data from the Korean Nationwide Lung Cancer Registry

Abstract: Lung cancer in Korea occurs predominantly in elderly patients, with adenocarcinoma being the most frequent subtype. The prognosis was poorer in ever-smokers and older, malnourished, and untreated patients with advanced lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
48
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 40 publications
10
48
4
1
Order By: Relevance
“…The crude incidence rate was reported to be 35.1 per 100 000 in Korea . About 81.8% of lung cancer is histologically classified as non‐small cell lung cancer (NSCLC), with a five‐year survival rate of only 22.1% . The main reason for this dismal prognosis is that about 70% of the patients with NSCLC are diagnosed at stage III or IV …”
Section: Introductionmentioning
confidence: 99%
“…The crude incidence rate was reported to be 35.1 per 100 000 in Korea . About 81.8% of lung cancer is histologically classified as non‐small cell lung cancer (NSCLC), with a five‐year survival rate of only 22.1% . The main reason for this dismal prognosis is that about 70% of the patients with NSCLC are diagnosed at stage III or IV …”
Section: Introductionmentioning
confidence: 99%
“…The leading histopathologic subtype had changed from squamous cell carcinoma to adenocarcinoma [19]. While squamous cell carcinoma was the leading subtype in males, adenocarcinoma showed the highest incidence in females [6].…”
Section: Discussionmentioning
confidence: 99%
“…A recent Korean lung cancer epidemiology study showed that the most frequent histological subtype was adenocarcinoma [5]. Although squamous cell carcinoma was the most common subtype in male patients, adenocarcinoma was the most common subtype in female patients [6]. A few studies have looked at variations in lung cancer histology in relation to fine particulate matter, and only one study has found no clear relationships between exposure to fine particulate matter and specific histologic cancer type [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, only patients diagnosed with adenocarcinoma were included in this study. Although adenocarcinoma is reported as the most common histologic type of lung cancer in South Korea, further evaluation is needed to determine whether this procedure will be effective in other cell types of lung cancer. The systemic antitumor effect of intrapleural docetaxel therapy, such as disease progression or mortality, also may need to be studied with a longer study period.…”
Section: Discussionmentioning
confidence: 99%